Effects of Lexical Competence on the Reading and Writing Ability of Grade 11 Science Students at Azezo High School, Gondar - Abtew, Gashaw (Ethiopian Renaissance Journal of Social Sciences and the Humanities, 2021)
The study investigated effects of lexical competence on students' reading and writing abili- ty through ex post facto research design. From eight sections, two randomly selected classes of 119 students were involved in the study. Lexical competence was measured through testing the size, depth and productive dimensions of vocabulary knowledge using VLT, WAT and vo- cabprofiler instruments respectively. Reading and writing abilities were measured using TOE- FL, and above-average and below-average reading /writing ability groups were created based on sample means. Group difference on vocabulary scores was tested using MANOVA. The find- ings showed that above-average readers scored significantly higher than below average readers on the size and depth dimensions, depth accounting for much of the variance. Above-average writers also scored significantly higher than below average writers, much of the difference be- ing accounted for by the productive dimension. The findings suggest that learners' reading and writing performance difference is largely attributed to the variance of their lexical competence.